Oral yeast colonization in patients with eating disorders: commensal acquisition or due to purgative habits? - Esteves, Camilla Vieira (2020)
Oral problems are common in patients diagnosed with Eating Disorders (ED) and still require better elucidation. We aimed to analyze the prevalence of oral Candida spp in individuals with ED. The sample of the study was comprised of 30 women with purgative habits and 15 without purgative habits. Samples of the oral cavity were collected by sterile cotton swab rubbed on soft tissues and teeth. Yeasts were isolated on Sabouraud dextrose agar. Yeasts were isolated from the oral cavity of 53% of the patients yielding 75 yeast isolates; of these, 43 were identified by conventional mycological methods: C. parapsilosis (n=19), C. glabrata (n=16), Rhodotorula sp (n= 6), C. famata (n=2). The remaining 32 isolates were presumptively identified as C. albicans or C. dubliniensis and required mass spectrometry for the final differentiation: 28 isolates were confirmed as C. albicans and four as C. dubliniensis. Among the control group, only four subjects (26.7%) were found to harbor C. albicans. The four C. dubliniensis isolates were from two patients, one that was only colonized and the other, with severe ED, was diagnosed with an oral candidiasis as demonstrated by the presence of pseudohyphae on the direct mycological exam from different sites. The increased rate of isolation of non-albicans species, such as C. glabrata, C. parapsilosis, and C. dubliniensis in the oral cavity from ED patients with nutritional deficiency may suggest that purgative habits of these patients can lead to changes in normal flora and predispose to oral candidiasis.